Causes of Online Gambling Entangling Gen Z - Hanuun Dzaki; Khadijah Khadijah; Muthiah Asma; Rizki Wulan Suci; Sofwah Hasanah; Urmila Sakhinah; Febryan Hidayat (Walidem Institute and Publishing, 2024)
The problem in this study is online gambling addiction in Gen Z. The purpose of this study is to determine the factors that cause online gambling in Gen Z, to find out the phenomenon of online gambling in the adolescent environment, to find out the criminal law of online gambling, to find out the impact of online gambling, to find out efforts to overcome online gambling. The research used is qualitative and in collecting data using the library assert method. This research uses secondary data sources, namely data related to information from pre-existing sources such as important documents, websites, and so on. The subject of this study is Gen Z. The results showed that the factors causing online gambling are environmental factors, desires, and profits, phenomena that occur in the current era of globalization are faced with certain patterns of social behaviour, people's social behavior tends to change along with the development of a complex era due to technological advances, mechanization, industrialization, and urbanization, criminal law is based on mistakes both intentional and negligence. Someone who is a legal customer must be held criminally accountable, psychologically, the impact of online gambling makes them introverted, meaning they stay away from others and prefer to be alone with their mobile phones rather than follow social activities carried out by others in their environment, the theory of countermeasures that have been done for online gambling crimes, namely preventive and repressive efforts. This preventive countermeasure focuses more on prevention before the crime occurs and is indirectly carried out without using criminal means or criminal law. Meanwhile, repressive efforts are carried out by looking directly for the root of the problem in the community to eradicate a crime by providing firm action so that criminals get a deterrent effect.